Upaya Meningkatkan Keaktifan Siswa dengan Menggunakan Metode Co-Op Co-Op Pada Pembelajaran PAI - Fuad Hasan; Eliyanto Eliyanto; Fibriyan Irodati (Tarbi: Jurnal Ilmiah Mahasiswa, 2023)
This study aims to describe the success of using the Co-op Co-op method on student activity in PAI learning in class XI IPA SMA VIP Al Huda Jetis Kebumen. The design of this research is Classroom Action Research (CAR). The research subjects were students of class XI IPA SMA VIP Al Huda Jetis, Kebumen. in the odd semester of T.A 2022/2023. The research was carried out in 2 cycles on the subject of Faith in Allah's Books and Dare to Live Honestly. Data was collected using teacher and student observation sheets, interviews, field notes, and documentation. Technical data analysis consists of four components, namely starting from data collection, data reduction, data display, and drawing conclusions. The results showed that before the Co-op Co-op type of cooperative learning model was applied, the PAI learning activity level of students still tended to be passive, but after the Co-op Co-op type of cooperative learning was applied, the following steps were taken: Class discussion focused on students , team selection and team formation, team topic selection, small topic selection, small topic preparation, small topic presentation, team presentation preparation, team presentation and evaluation of student activity have increased. Increased student activity is indicated by the presence of students' attention to the teacher's and friends' explanations, taking notes on learning materials, daring to ask questions, daring to answer and expressing opinions, actively participating in group discussions, writing down the results of their discussions, daring to present the results of discussions in front of the class, and daring to give responses. against other groups.